2015
DOI: 10.1098/rsta.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical water oxidation for the destruction of hazardous waste: better than incineration

Abstract: Supercritical water oxidation (SCWO) is an advanced process mainly employed for the treatment of hazardous stable wastes, otherwise treatable by incineration. It is based on the unique properties of water above its critical point (T(c)=675 K, P(c)=22.2 MPa), making it a superior reaction medium for the destruction of all organics in the presence of oxygen. This work presents preliminary laboratory scale studies on SCWO of nitrogen (N)-containing hazardous hydrocarbons, with a view to enhancing the process perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…On the other hand, IPA addition enhanced TN% removal by a significant 66% raising it to over 85% N removal at 450C. The effect has been observed in literature [20,14]…”
Section: Effect Of Oxidant Ratiosupporting
confidence: 62%
“…On the other hand, IPA addition enhanced TN% removal by a significant 66% raising it to over 85% N removal at 450C. The effect has been observed in literature [20,14]…”
Section: Effect Of Oxidant Ratiosupporting
confidence: 62%
“…Enhancement of SCWO of DMF was also investigated using multi-port oxidant injection [13,14], which showed improved TOC % conversion and N speciation upon gradual oxidant feed. Other studies confirmed the positive influence of IPA addition to SCWO of DMF, in view of process enhancement [15,16]. (at 20°C).…”
Section: Introductionmentioning
confidence: 57%
“…For this, the SCWO systems differ from SCWGs in the feeding section, as proper mixing and preheating of the feed, water, and oxidant streams should be achieved before the reaction. In this view, feeding systems based on oxidant multiinjection at different reactor points has been proposed to avoid the corrosion and salt deposition problems [93][94][95]. It was found that oxidant dosage in a SCWO reactor is also an aspect in energy management [93].…”
Section: Supercritical Water Oxidationmentioning
confidence: 99%